THE INFLUENCE OF EDUCATION ON COMMUNITY INCOME GAPS:A CASE STUDY IN THE EAST JAVA REGION - Daffa Mustika Suryadinata; Norman Sahrul Bahtiar; Alfina Nur Hidayah; Amanatus Sholihah (WORLDVIEW ( Development economic and sharia studies journal ), 2023)
Abstract Education is one of the main factors that causes income inequality in society.This study aims to investigate the impact of education on income inequality in East Java. The testing method in this study uses a quantitative method by using annual time series data from the education index and Gini ratio in the districts/cities of East Java as the research sample. According to the results of the study, education has a significant correlation with income. A person with a high level of education is more likely to earn a high income. This is due to several factors, including: increased productivity, increased access to employment, and increased social mobility, as education can help someone improve their social status. Therefore, this study is expected to help the government improve access and quality of education in East Java, this is important to reduce income inequality. By understanding the relationship between education and income, the government can design more effective and sustainable policies for the economic development of East Java. Keywords: education, income inequality, economic development